1988
DOI: 10.1111/j.1464-410x.1988.tb04364.x
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen Pre‐treatment Abolishes Luteinising Hormone‐Releasing Hormone Testosterone Stimulation

Abstract: In patients with histologically confirmed prostate cancer, oestrogen priming with diethylstilboestrol (DES) (3 mg/day) for 4 weeks prior to the first injection of the LHRH agonist Zoladex (3.6 mg depot form) prevented any rise in the serum testosterone concentration. In contrast, in the groups pre-treated with DES, the first, but not subsequent, injections with Zoladex were associated with a marked surge in luteinising hormone. Treatment with DES beyond the time of the first administration of Zoladex did not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…5 Since Trachtenberg's 6 report that disease flare could be suppressed by the preadministration of estrogen, various therapies have been employed to suppress flare. 4,[7][8][9][10] We have demonstrated that pretreatment with diethylstilbestrol diphosphate (DES-P) and chlormadinone acetate (CMA) inhibited disease flare. 11 A nonsteroidal pure antiandrogen, flutamide (FLU) has also been used to prevent disease flare.…”
Section: Introductionmentioning
confidence: 99%
“…5 Since Trachtenberg's 6 report that disease flare could be suppressed by the preadministration of estrogen, various therapies have been employed to suppress flare. 4,[7][8][9][10] We have demonstrated that pretreatment with diethylstilbestrol diphosphate (DES-P) and chlormadinone acetate (CMA) inhibited disease flare. 11 A nonsteroidal pure antiandrogen, flutamide (FLU) has also been used to prevent disease flare.…”
Section: Introductionmentioning
confidence: 99%
“…In these 5 patients, PSA levels decreased during pretreatment and remained well beneath pretreatment levels. The mean absolute values of serum testosterone in each treatment group are shown in Tsushima/Nasu/Saika/Maki/Noda/Suyama/ Yamato/Kumon [5] G DES 3 mg -28F T + Takeuchi et al [6] G DES-DP 500 mg i.v. -7,0F T, PAP, PSA -7:+, 0:-Shimizu et al [7] G ECT 560 mg -21F PAP, PSA + Boccon-Gibod et al [8] Buserelin CPA 300 mg -7F T + Schulze and Senge [9] G CPA 200 mg -7F T, PAP + Bruchovsky et al [10] G CPA 100 mg + DES 0.1 mg -28F T, PAP, PSA + Yoshida and Takeuchi [11] L CMA 100 mg -28, -14F T, PSA -28:+, -14:B Yamamoto et al [12] G or L CMA 100 mg -28, -14F T, PSA + Kuhn et al [13] Buserelin Niltamide 300 mg 0F PSA + Labrie et al [14] D-Trp 6 Gn-RH Flutamide 750 mg -1F PAP + Schulze and Senge [9] G Flutamide 750 mg -7, -1F PAP -7:+, -1:B Present study L Flutamide 375 mg -28, -14, -7,0F PSA + GnRHa = Gonadotropin-releasing hormone agonist; G = goserelin; L = leuprorelin; T = testosterone; PAP = prostatic acid phosphatase; PSA = prostate specific antigen; DES = diethylstilbestrol; CPA = cyproterone acetate; ECT = estramustine phosphate; DES-DP = fosfestrol; CMA = chlormadinone acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that pretreatment with diethylstilbestrol (DES) for 1 week did not completely suppress the transient increase in testosterone, whereas pretreatment for 4 weeks completely suppressed the transient increase [3][4][5]. Takeuchi et al [6] reported that after intravenous injection of DES-diphosphate (fosfestrol; DES-DP) for 1 week, testosterone transiently increased after administration of the GnRH agonist, but the PSA did not exceed its pretreatment level.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of DES for 28 days is reported to prevent any rise in testosterone during goserelin therapy [12], However, it must be remembered that, despite the limited dose and duration of treatment, the patients are still at risk of cardiovascular complications. ECT is re ported to be associated with milder cardiovascular com plications than is low-dose DES [5].…”
Section: Discussionmentioning
confidence: 99%